2014
DOI: 10.1038/nrurol.2014.243
|View full text |Cite
|
Sign up to set email alerts
|

Emerging mechanisms of enzalutamide resistance in prostate cancer

Abstract: The majority of prostate cancers are hormone-dependent at diagnosis highlighting the central role of androgen signalling in this disease. Surprisingly, most forms of castration-resistant prostate cancer (CRPC) are still dependent on the androgen receptor (AR) for survival. Therefore, the advent of new AR-targeting drugs, such as enzalutamide, is certainly beneficial for the many patients with metastatic CRPC. Indeed, this compound provides a substantial survival benefit-but it is not curative. This Perspective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
107
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(108 citation statements)
references
References 42 publications
1
107
0
Order By: Relevance
“…By preventing androgen binding to AR, enzalutamide inhibits the nuclear localization and transcriptional activity of AR (39). Despite the early clinical benefits, most patients eventually developed enzalutamide resistance due to reactivation of the AR signaling pathway by various mechanisms including AR truncation and point mutations (9). Here, three different PCa cell lines were used to test whether HSP90 inhibitors (17-AAG and GA) would sensitize cells to enzalutamide treatment.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…By preventing androgen binding to AR, enzalutamide inhibits the nuclear localization and transcriptional activity of AR (39). Despite the early clinical benefits, most patients eventually developed enzalutamide resistance due to reactivation of the AR signaling pathway by various mechanisms including AR truncation and point mutations (9). Here, three different PCa cell lines were used to test whether HSP90 inhibitors (17-AAG and GA) would sensitize cells to enzalutamide treatment.…”
Section: Resultsmentioning
confidence: 99%
“…Consequently, drugs targeting AR pathway such as enzalutamide have been used for CRPC patients. Although the drug provides a substantial survival benefit, patients develop enzalutamide resistance eventually due to re-activation of AR (9). Thus, new strategies targeting the AR signaling pathway are needed to overcome enzalutamide resistance.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, recent clinical trials have shown that the AR antagonist MDV3100 (MDV)11 and abiraterone, an inhibitor targeting androgen synthesis12, are effective against CRPC. However, recent studies have reported that AR-Vs which lack the LBD are resistant to anti-androgen therapy including MDV and abiraterone1314151617. Since the major AR-Vs identified to date have an intact N-terminal domain and DNA-binding domain, they display constitutive activity, which underlies the persistent AR signalling in CRPC expressing these variants6181920.…”
mentioning
confidence: 99%
“…In addition, an understanding of the mechanisms behind abiraterone (Romanel et al 2015) and enzalutamide resistance (Claessens et al 2014), and whether this is linked to altered androgen and oestrogen metabolism, will be required before the next big step is taken towards development of endocrine therapy for prostate cancer.…”
Section: Resultsmentioning
confidence: 99%